(untitled) (Global Journal of Science Frontier Research, 2014)
This paper is the second part of a TETFUND sponsored research carried out to examine trends of climatic variables in Taraba State Nigeria. Previous studies concentrated on the evidence of climate change in the state, awareness of climate change among students of tertiary institutions in the state and farmers perception and adaptation to climate change in northern Taraba. There is need to examine the trend and pattern of climatic variables in the whole state. This knowledge gap may greatly reduce the failures in measures to develop a state wide effective monitoring, adaptation and mitigation measures to climate change in the study area. Climatic data such as mean monthly and annual temperature and rainfall totals and rain days per annum for the four meteorological stations in the state (Lau, Gassol, Ibi and Gembu) for a period of 30 to 35 years was obtained. These were used in calculating the mean temperature, mean monthly rainfall, annual rainfall, the onset, cessation and length of rainy season. The result shows that all the stations exhibited a similar trend of increasing temperature with exception of Gembu where the temperature is decreasing. Annual rainfall show increasing trend in the southern and central part of the state with exception of Lau in the northern part of the state.